Effects of aspirin on small-cell lung cancer mortality and metastatic presentation. (April 2017) - Maddison, Paul
Highlights: Aspirin has been shown to reduce cancer incidence and mortality, including lung cancer. Data on the effects of aspirin on small-cell lung cancer (SCLC) are sparse, and conflicting. We have shown in multivariate analysis of a large cohort of patients with SCLC that aspirin does not improve cancer survival. Abstract: Although meta-analysis data have shown that taking regular aspirin may reduce lung cancer mortality, individual trial data results are conflicting, and the data on the effects of aspirin on different histological subtypes of lung tumours, in particular small-cell lung cancer, are sparse. We conducted a prospective observational study of 313 patients with a new diagnosis of small-cell lung cancer and recorded use of aspirin before and after tumour diagnosis. Seventy-one (23%) patients were taking regular daily aspirin for more than 2 years at the time of tumour diagnosis. We found that regular use of aspirin had no effect on survival nor metastatic presentation compared to data from small-cell lung cancer patients not taking aspirin. The lack of survival benefit in patients with small-cell lung cancer taking long-term aspirin may be due to the low expression of cyclooxygenase-2 in small-cell lung cancer tissue.